DIDACTIC ENGINEERING OF THE IT-DISCIPLINE’s CONTENT OF PEDAGOGICAL EDUCATION (Journal of Information Technologies in Education (ITE), 2013)
The author substantiates the content of stages of the didactic engineering of information technology discipline in higher pedagogical education.
Keywords: design; engineering; informational educational product; the skills of product-technology practice